Descripción de el simulador de producción de energía eólica utilizando metodología STEAM acorde al currículo del subnivel medio de Educación General Básica - Macas Ordoñez, Genesis Alejandra (2023)
The STEAM methodology, which has recently appeared in our educational environment, is characterised by being interdisciplinary, as it works together with the areas of knowledge (Science, Technology, Engineering, Art and Mathematics), and also allows the design and creation of resources such as models, prototypes, games and other learning materials, which are used to teach concepts of the areas of knowledge in a practical and active way. Also, by creating resources, students can learn effectively and strengthen their skills such as creativity, critical thinking and problem solving. The present research aims to analyse the wind energy production simulator using STEAM methodology according to the curriculum of the intermediate sub-level of General Basic Education (EGB); In this sense, the research is of a descriptive exploratory type, and as an instrument we used the curricular contents provided by the Ministry of Education, the STEAM methodology and its phases proposed in the Instructional Framework (understand, imagine, design, build, approve and improve), for the description of the wind energy simulator project, the procedure of its design and construction was detailed, also through the simulator 4 cards were generated based on the support guide for teachers in the implementation of STEAM methodology provided by the Ministry of Education, In this way, the construction of projects such as the wind energy production simulator using STEAM methodology in the educational context, helps students to put theoretical content into practice, relating the topics of the curriculum of the intermediate sub-level of EGB with respect to renewable energy with the Sustainable Development Goals 4 and 7 (SDGs) through practical experimental activities that contribute to socialisation and knowledge for students to apply in the future. Keywords: STEAM; methodology; education; interdisciplinary; simulator; innovation; SDGs.